Antioxidant and Hepatoprotective Activity of Livina, A Polyherbal Liquid Formulation - Darbar, Soumendra; Ghosh, Bhaskar; Chattapadhyay, Shyamaprasad; Ranjan Chakraborty, Matish (Asian Journal of Chemistry, 2010)
Alcohol dependency is a major health and socio-economic problem throughout the world. Hepatic damage by alcohol, alcohol consumption in one from or the other has become almost a routine in the hectic modern world. After heart disease and cancer, alcoholism is the world's biggest health problem and most deaths attributed to alcoholism are caused by cirrhosis of the liver. Damaging effects of reactive oxygen species (ROS) on living systems are well documented. They include oxidative attack on vital cell constituents. Results show that Livina, a polyherbal liquid formulation was effective in blunting ethanol-induced enhanced activities of serum glutamate oxaloacetate transaminase (SGOT), serum glutamate pyruvate transaminase (SGPT), alkaline phosphatase (ALP), level of serum bilirubin (both total and direct), serum total cholesterol, liver weight loss was also effective in reducing ethanol-induced lipid peroxidation. Livina on the other hand was also effective in blunting ethanol-induced suppressed activities of superoxide dismutase (SOD), catalase (CAT) and decreased level of reduced glutathione (GSH). Results of hepatocellular damage caused by ethanol and its recovery by Livina, suggest that it might be considered as a potential source of natural hepatoprotective agent, which could be related to the free radical scavenging properties.